Residential child care and foster care: Critical comparative analysis on literature - Chan, Cheong Chong (2015)
Residential child care and foster care are two popular substitute placements for children who are separated from their birth families.Various claims and comments have been made on both placements.Some are empirically supported, but some are merely personal beliefs.Unexamined claims and comments might have influenced social workers in their practices and research.Hence, this article presents a brief review of the literature in residential child care and foster care. For this purpose, a comparative analysis on 42 residential child care literature and 49 foster care literature was conducted Outcomes of the analysis show that three main themes can be generated.The themes are research design, professionalism of caregivers and children’s problems.In brief, child-centric perspective, comparison group and longitudinal designs were not commonly used in studies on both placements. Training for caregivers in both placements was highly discussed.Behaviour, education, and health issues were the common issues for children residing in both placements.Overall, both placements share a similar focus in practices and research.This implies that a comparative design to examine both placements concurrently could be a practical research design in future.